INSTAGRAM SEBAGAI MEDIA INFORMASI KONSERVASI: EVALUASI SOSIO-DEMOGRAFI PENGIKUT AKUN @bbtn_gn_gedepangrango - Afiyanti, Sisca Widiya; Soekmadi, Rinekso; Rachmawati, Eva (Universitas Nusa Bangsa, 2025)
Social media has become a crucial platform for disseminating tourism-related information, including climbing tourism within conservation areas. Mount Gede Pangrango National Park (TNGGP) utilizes the Instagram account @bbtn_gn_gedepangrango to share information about hiking activities, promote nature-based tourism, and provide education on conservation ethics through the #PendakiCerdas campaign. This study aims to evaluate the management of the @bbtn_gn_gedepangrango account based on the socio-demographic characteristics of its followers. Data were collected from 482 active followers using a quantitative approach through an online questionnaire. The findings indicate that the majority of followers belong to Generation Z, are male, have a high school level of education, and reside in the Greater Jakarta area (Jabodetabek). However, the level of concern regarding waste management remains low, as only 19% of respondents demonstrated awareness of waste issues within TNGGP. These results highlight the need for more targeted and audience-specific conservation communication strategies to enhance public awareness and participation in environmental preservation efforts.